Možnosti zatraktivnění železniční trati 122 na území Prahy - Votava, Martin; Votava Martin (České vysoké učení technické v Praze, 2015)
Předmětem bakalářské práce "Možnosti zatraktivnění železniční trati 122 na území Prahy" je provést analýzu současného stavu železniční trati a provozu na ní a zhodnotit současnou i plánovanou zástavbu, kterou trať prochází. Na základě této analýzy pak navrhnout umístění nových železničních zastávek a provozní koncept umožňující lepší využití tratě v městské dopravě.

The subject of the bachelor-work "Possibilities of getting railway track number 122 in Prague more attractive" is an analysis of contemporary state of the railway-track and its traffic and an evaluation of the present and planned built-up area the railway-track passes through. Then, on the basis of this analysis, the work is to suggest a location of new railway-stations and a traffic draft making a better use of the track in city transport possible.
Possibilities of Getting Railway Track Number 122 in Prague More Attractive
Keywords: Jízdní doby, PID, Provozní koncept, Přepravní průzkumy, Úpravy infrastruktury, Železniční trať 122, Železniční zastávky; Travel times, Prague Integrated Transport, Traffic concept, Numbers of passengers, Changes of infrastructure, Railway track number 122, Railway stops